Lower Portion of Kingstown with Fort Charlotte Left Kingstown, St. Vincent, B.W.I - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2023)
Scenic view of the lower portion of Kingstown with Fort Charlotte left, Kingstown, St. Vincent, British West Indies. Houses and other buildings are situated are various points of the area. Trees, shrubs and bushes are also seen covering the area. A partial mass of a mountain is seen in the distance. In the background a view of the ocean is seen. This is a divided back postcard. Back of the postcard West Indies (H) NP £12 (Handwritten in pencil). Inland 1/2d Foreign 1 d (stamp corner). Made in Germany Schiebeler & Co. Hamburg.
Landscape; Colour; 3 ½” x 5 ½”
Keywords: Trees; Houses; Buildings; Hills; Forts and fortifications; Aerial views; Aerial photographs; Panoramic views; Cities and towns; Fort Charlotte